MODEL PENINGKATAN KNOWLEDGE SHARING BERBASIS MODAL SOSIAL DAN LEARNING ORGANIZATIONTERHADAP KINERJA AGENCY PADA PT PRUDENTIAL LIFE ASSURANCE - Athoillah Athoillah (Jurnal Ekonomi dan Bisnis, 2017)
The role of human resources reliable and professional in order to increase performance isneeded, because it will affect the survival of the company. The phenomenon that often occursin PT Prudential Life Assurance is the declining performance of the agency in the search for lifeinsurance customers indicated by the number of customers. The purpose of this research is toinvestigate and analyze the influence of social capital and learning organization of the agency’sperformance in PT Prudential Life Assurance with knowledge sharing as an intervening variable.The population is all the marketing power PT Prudential HD Agency Semarang are still active by67 employees. Given a population of only 67 employees, it deserves to be taken as a whole tobe sampled, so this study is a census study. A tool of analysis is path analysis, which previouslytested the validity and reliability and classic assumption test. The test results indicate socialcapital proved to have a positive effect and significant knowledge sharing. Learning organizationhas a positive and significant impact on knowledge sharing. Social capital, learning organizationand knowledge sharing proved to have a positive and significant impact on the performance ofthe agency. Knowledge sharing is not able to become an intervening variable between socialcapital with the performance of the agency. Knowledge sharing is able to become an interveningvariable between learning organization with the performance of the agency, meaning that thehigher awareness of the company in increasing the capacity of learning for employees, itwill raise the height of employees to share knowledge and it certainly will impact on the highperformance of the agency.Keywords: Social capital, learning organization, knowledge sharing and performance agency